Solomon Islands : Economic Development Documents- Medium-Term Development Plan, 2016-20. (IMF Staff Country Reports; Country Report ;, 2016)
This report describes Solomon Islands' macroeconomic, structural, and social policies in support of growth and poverty reduction, as well as associated external financing needs and major source of financing. Solomon Islands' government Medium Term Development Plan (MTDP) 2016-20 sets out development programs and projects supporting the draft National Development Strategy (NDS) 2016-35 objectives. The MTDP is rolling out five-year plan, revised annually, comprising development programs and projects. The MTDP effectively addresses key issues of the economy which are as follows: existing poverty situation and trends, factors influencing poverty, strategies and policies for poverty reduction, fiscal and debt framework, and safety nets and risk mitigation.